2009
DOI: 10.1007/s10865-009-9200-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-efficacy and physical activity among patients with type 2 diabetes

Abstract: Results supported a mediation effect, such that the treatment effect on physical activity was completely mediated by changes in self-efficacy. Although replication is needed, results support the theoretical rationale for targeting self-efficacy to promote physical activity among patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 42 publications
5
59
3
2
Order By: Relevance
“…Self-efficacy (an individual's intrinsic confidence in their ability to perform a specific task) is a construct that has been associated with successful behavioral change, including increasing physical activity. [28][29][30][31][32][33] Self-efficacy is by its very nature a task-specific construct. 34 The Self-Efficacy scale used in this study is a general scale designed to broadly assess self-efficacy for dealing with chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy (an individual's intrinsic confidence in their ability to perform a specific task) is a construct that has been associated with successful behavioral change, including increasing physical activity. [28][29][30][31][32][33] Self-efficacy is by its very nature a task-specific construct. 34 The Self-Efficacy scale used in this study is a general scale designed to broadly assess self-efficacy for dealing with chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with belief in their ability to exert control over a behavior showed a stronger tendency to avoid smoking, drink less, consume a healthy diet, and exercise regularly. Research has shown that there is a statistically significant positive relationship between self-efficacy and health behaviors, including smoking cessation (Leung et al, 2008), reduction in alcohol consumption (Oei et al, 2007), fruit and vegetable intake (Anderson et al, 2007), and physical activity (Morris et al, 2008;Dutton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy for exercise has been shown to increase physical activity (PA) levels in diabetic patients [5]. As a result of intervention-based SCT, improvements in PA levels are maintained for 6 -12 months [6].…”
Section: Introductionmentioning
confidence: 99%